Sejarah dan Ruang Lingkup Perbankan Syari’ah di Indonesia - Afriyadi, Afriyadi; Aisyah, Siti (MUI Kota Pekanbaru, 2024)
Sharia banking is basically a banking system whose business is based on the principles of Islamic law with refernce to the Al-Qur’an and Al-Hadist. This writing uses a type/approach method in the form of library research. The practice of sharia banking began during the time of Rasulullah SAW. in the beginning, Islamic finance began at the beginning of Islamic 1,400 years ago. History written in the early years of Islamic show that in the 1st century of Islamic (600 AD) there was a form of banking activity that was similar to modern banking transactions, namely Al-Zubair bin Al-Awam. After that, sharia banking developed in Indonesia, Bank Muamalat was the first to be established in 1992. Banks are business entities that collect funds from the public in the form of savings and distribute them to the public in the form of credit and/or other forms to improve people’s living standards. Meanwhile, Sharia Bank are banks that carry out their business activities based on sharia principles and acording to their type consist of Sharia Commercial Banks and Sharia People’s Financing Banks. The principle of Ridha’iyyah (willing and willing), the principle of justice, and the principle of mutual benefit.